Food shelf life stability : (CRC Press, 2001)
Food Shelf Life Stability presents the fundamental principles for maintaining high quality in food over an extended period. It discusses the physical, biochemical, and microbiological factors that affect the self life of food products and the variables that can enhance their stability.